The design and implementation of a web-based software tool for benchmarking collaborative editing algorithm - Wang, Ye. (2011)
With a rapid development of today’s Internet, there has been an increasing demand for multi-user real-time collaborative systems. Numbers of researches have been conducted in order to find out comprehensive solutions for collaborative systems. Among them Operation Transformation (OT) Technique is an important approach to support real-time collaborative applications. Due to the complexity of operational context in OT, a testing tool is necessary to analyze and evaluate such kind of systems.